Sustained Intra-Articular Release and Biocompatibility of Tacrolimus (FK506) Loaded Monospheres Composed of [PDLA-PEG1000]-b-[PLLA] Multi-Block Copolymers in Healthy Horse Joints - Stefan M. Cokelaere; Wilhelmina M.G.A.C. Groen; Saskia G.M. Plomp; Janny C. de Grauw; Paul M. van Midwoud; Harrie H. Weinans; Chris H.A. van de Lest; Marianna A. Tryfonidou; P. René van Weeren; Nicoline M. Korthagen (MDPI AG, 2021)
There is an increasing interest in controlled release systems for local therapy in the treatment of human and equine joint diseases, aiming for optimal intra-articular concentrations with no systemic side effects. In this study, the intra-articular tolerability and suitability for local and sustained release of tacrolimus (FK506) from monospheres composed of [PDLA-PEG1000]-b-PLLA multiblock copolymers were investigated. Unloaded and tacrolimus-loaded (18.4 mg tacrolimus/joint) monospheres were injected into the joints of six healthy horses, with saline and hyaluronic acid (HA) in the contralateral joints as controls. Blood and synovial fluid were analysed for the tacrolimus concentration and biomarkers for inflammation and cartilage metabolism. After an initial burst release, sustained intra-articular tacrolimus concentrations (>20 ng/mL) were observed during the 42 days follow-up. Whole-blood tacrolimus levels were below the detectable level (<0.5 ng/mL). A transient inflammatory reaction was observed for all substances, evidenced by increases of the synovial fluid white blood cell count and total protein. Prostaglandin and glycosaminoglycan release were increased in joints injected with unloaded monospheres, which was mitigated by tacrolimus. Both tacrolimus-loaded monospheres and HA transiently increased the concentration of collagen II cleavage products (C2C). A histologic evaluation of the joints at the endpoint showed no pathological changes in any of the conditions. Together, these results indicate the good biocompatibility of intra-articular applied tacrolimus-loaded monospheres combined with prolonged local drug release while minimising the risk of systemic side effects. Further evaluation in a clinical setting is needed to determine if tacrolimus-loaded monospheres can be beneficial in the treatment of inflammatory joint diseases in humans and animals.